2014
DOI: 10.1371/journal.pone.0093612
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Effect of Pneumonia on Surfactant Disaturated-Phosphatidylcholine Kinetics in Newborn Infants

Abstract: BackgroundBacterial pneumonia in newborns often leads to surfactant deficiency or dysfunction, as surfactant is inactivated or its production/turnover impaired. No data are available in vivo in humans on the mechanism of surfactant depletion in neonatal pneumonia. We studied the kinetics of surfactant's major component, disaturated-phosphatidylcholine (DSPC), in neonatal pneumonia, and we compared our findings with those obtained from control newborn lungs.MethodsWe studied thirty-one term or near-term newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The administration of a tracer dose of (U-13 C-PA)dipalmitoyl-phosphatidylcholine allowed us to measure the DSPC kinetics, confirming previous findings of our research group (15). We found that in newborns with pneumonia DSPC PS and t 1/2 are, respectively, lower and shorter compared to controls.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The administration of a tracer dose of (U-13 C-PA)dipalmitoyl-phosphatidylcholine allowed us to measure the DSPC kinetics, confirming previous findings of our research group (15). We found that in newborns with pneumonia DSPC PS and t 1/2 are, respectively, lower and shorter compared to controls.…”
Section: Discussionsupporting
confidence: 88%
“…If additional parental consent was obtained, we also measured DSPC turnover with a tracer dose of (U-13 C-PA)dipalmitoyl-phosphatidylcholine mixed with 2-5 mg/kg of Curosurf, used as a spreading agent. Administration of the tracer dose and TA collection and processing were performed as previously reported (15,31). Processed samples were stored at −80 °C until analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of this (or: the described) mechanism on the course of infection and cellular damage can only be speculated about. During pneumococcal pneumonia, surfactant breakdown and impaired surfactant synthesis are hallmarks of infection in the alveolar epithelium and contribute to its severity (62,63). In the healthy lung, surfactant secretion is regulated by purinergic signaling and mediated by ATP in a paracrine manner.…”
Section: S Pneumoniae Inhibits P2y 2 Signalingmentioning
confidence: 99%
“…Respiratory disorders reflect the severe destruction of lung tissue associated in particular with the deficiency or dysfunction of the surfactant [42]. Differential diagnosis of respiratory pathologies of non-infectious origin and congenital pneumonia in premature infants still remains an unsolved problem in neonatology.…”
Section: Urine Proteome Analysis For Newborns With Respiratory Diseasmentioning
confidence: 99%